The effect of ceramic bonder on shear bond strength at the metal-ceramic interface in casted and direct metal laser sintering cobalt-chromium alloy - An in vitro study - Nadipalli Sri Gowri; K. Mahendranadh Reddy; Y. Mahadev Shastry; S. Venkat Aditya; Divya Dubey (Wolters Kluwer Medknow Publications, 2024)
Aim: (1) The aim of this study was to evaluate the effect of a ceramic bonder at the metal ceramic interface in sintered and casted cobalt-chromium (Co-Cr) alloy. (2) To compare the shear bond strength between the different manufacturing techniques: Casting and direct metal laser sintering (DMLS). Setting and Design: In vitro comparative study. Materials and Methods: For the casting group, 40 clear acrylic patterns with dimensions of 20 mm × 10 mm × 2.5 mm were designed in a software and casted with Co-Cr alloy. For DMLS samples, a standard tessellation language file with the abovementioned dimensions was created through a software to fabricate 40 samples. All the samples were equally distributed into the following four groups: • Group A - Casted samples with the application of Cerambond (n = 20) • Group B - Casted samples without application of Cerambond (n = 20) • Group C - DMLS samples with application of Cerambond (n = 20) • Group D - DMLS without application of Cerambond (n = 20). Ceramic buildup was done on all 80 samples, followed by firing up to a temperature of 920°C in a ceramic furnace. SBS was evaluated using a universal testing machine and failure modes were examined under the electron microscope. Statistical Analysis Used: ANOVA test and Tukey's honestly significance difference post hoc test for multiple comparisons. Results: One-way analysis of variance test revealed that the shear load and bond strength values of all four groups were statistically different with P < 0.001. Post hoc Tukey's test showed statistically significant difference among the four groups. The mean shear strength of Group C was significantly greater when compared to other groups, respectively. Conclusions: Within the limitations of this study, the application of Cerambond to both casted and sintered samples showed significantly increased SBS values and it was also observed that sintered samples had higher strength than casted samples. Altogether, the results indicate that the use of Cerambond increased the shear strength between cobalt Cr alloy and ceramics, thereby prolonging the longevity of the restorations.